Cassava seedpreneurship, determinants of varietal adoption, profitability, and women empowerment in Nigeria - Olawale E. Olayide (Elsevier, 2021)
Cassava “seedpreneurship”, is an emerging concept that focuses on establishing a sustainable cassava seed system. The dearth of empirical studies on seedpreneurship and the gaps in understanding the adoption of improved cassava varieties, profitability of Village Seed Entrepreneurs (VSEs), and women empowerment led to this study. This study was carried out in Nigeria using a multi-stage sampling method. It covered the four states (Abia, Akwa-Ibom, Benue, and Oyo) where VSEs and out-growers’ farming activities were carried out under the Building an Economically Sustainable Integrated Seed System for Cassava (BASICS I) Project. A total of 901 respondents were sampled. Structured questionnaires were administered during interviews. The conceptual framework provides representative indicators with focus on varietal adoption as environmental and genetic resources (environmental sustainability), profitability (economic sustainability) and women empowerment (social sustainability). The data gathered were analysed using descriptive analysis, chi-square test, profitability analysis, and probit regression model. Factors that influenced the adoption of improved cassava stems were age, nearness to agro input dealers, gender, and source of stems. The profitability analysis revealed that 96 percent of the seedpreneurs recorded profits. The profit levels varied by scale of operation. Access to credit and input in productive decisions were the most important indicators of women empowerment in seedpreneurship. Overall, the study revealed that seedpreneurship drives varietal adoption, increases profitability, and enhances women empowerment within the context of sustainable cassava seed system in Nigeria. Project implementors and policymakers can benefit from the findings in developing a sustainable formal seed sector.